A risk-based approach to evaluating the Area of Review and leakage risks at CO2 storage sites. (February 2020) - White, Signe; Carroll, Susan; Chu, Shaoping; Bacon, Diana; Pawar, Rajesh; Cumming, Lydia; Hawkins, Jared; Kelley, Mark; Demirkanli, Inci; Middleton, Richard; Sminchak, Joel; Pasumarti, Ashwin
Highlights: The NRAP-IAM-CS was used to determine risk-based leakage impacts and the Area of Review at three potential CO2 storage sites. The risk-based Area of Review was smaller than that determined from analytical calculations for an over-pressurized reservoir. The NRAP-IAM-CS showed minimal influx of CO2 and brine through legacy wells with no impact to the USDW. This study provided an invaluable opportunity for testing and improving the NRAP-IAM-CS for quantifying risks at CCS sites. Abstract: The U.S. Environmental Protection Agency's Class VI regulations for underground carbon dioxide (CO2 ) injection require owners and operators of storage projects to identify (1) an Area of Review (AoR) that represents the region that may be affected by the injection of CO2, and (2) leakage risks that might impact the quality of underground sources of drinking water (USDWs). This article describes how such risks can be determined by accounting for the physical and chemical properties of all components of a CO2 storage site using elements of the National Risk Assessment Partnership Integrated Assessment Model for Carbon Storage (NRAP-IAM-CS). We used practical data from three sites that are part of two CarbonSAFE (Carbon Storage Assurance Facility Enterprise) projects to demonstrate application of the NRAP-IAM-CS toolset to determine project risk areas. NRAP-IAM-CS was used to estimate the project risk area that could represent the AoR and the impact of leakage through legacy wells to overlying drinking waters at these candidate CO2 storage sites. Our study shows that risk to USDWs is minimal despite (1) the presence of multiple legacy wells at these sites where the AoR approximates the maximum extent of injected CO2 or (2) the presence of a much larger AoR approximating the pressure front caused by the injection of CO2 .